The Social Divide: Impact of Gated Communities on Urban Interaction - Karrar Hamza Alkhafagie; Dheah Hameed Bassee (Academia Open, 2024)
This study delves into the social ramifications of gated communities, particularly their influence on urban social interaction and city segregation. Utilizing space composition methodology, the research hypothesizes that gated communities diminish social interaction and contribute to urban segregation. Through a comparative analytical approach, two residential projects in Holy Karbala Governorate were examined in their existing gated state and in a hypothetical non-gated scenario. The findings substantiate the hypothesis, revealing that gated communities indeed lower clarity and integration values, which are pivotal for understanding and interacting within urban spaces. While these communities exhibit high internal social interaction, they lack city-level social engagement, thereby not supporting the social logic theory. Furthermore, the isolation of these residential projects from the broader urban fabric is linked to diminished quality of life and inefficient urban space usage. The study highlights the negative implications of gated communities on urban social dynamics, underscoring the need for reconsidering urban planning and residential project designs to foster more inclusive and socially vibrant urban environments. Highlights : Gated communities significantly reduce clarity and integration in urban spaces, hindering broader social interaction and understanding of the urban environment. Despite fostering high internal social interaction, gated communities fail to support city-level social engagement, leading to urban segregation. The isolation of gated residential projects from the urban fabric contributes to a decreased quality of life and inefficient use of urban spaces. Keywords : Gated Communities, Urban Segregation, Social Interaction, Urban Planning, Space Composition Methodology